Private Tutoring and its Effect on Students’ Learning Performance - Shokirova, Makhbubakhon; Rasulov, Ikhtiyor (Journal of Language Development and Linguistics, 2024)
The study examines the global private tutoring industry, focusing on South Korea, China, and Japan. It examines factors like academic pressure, school excellence, and subject challenges. It highlights the widening achievement gap in middle school and the positive effects of sustained tutoring. The study also reveals the complex dynamics of tutoring in high school, with varying effects on academic performance. The findings will inform education stakeholders, policy makers, and researchers, emphasizing the need for tailored approaches and a more nuanced understanding of tutoring's role in shaping students' educational pathways.